2011
DOI: 10.1088/1748-6041/6/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable polycaprolactone-chitosan three-dimensional scaffolds fabricated by melt stretching and multilayer deposition for bone tissue engineering: assessment of the physical properties and cellular response

Abstract: Fabrication of polycaprolactone (PCL)-chitosan (CS) three-dimensional (3D) scaffolds using the novel technique of melt stretching and multilayer deposition was introduced. In brief, firstly, the PCL-CS monofilaments containing 0% (pure PCL), 10%, 20% and 30% CS by weight were fabricated by melting and stretching processes. Secondly, the desired multilayer (3D) scaffolds were fabricated by arranging and depositing the filaments. Physical properties of the filaments and the scaffolds were evaluated. MC3T3-E1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Polymers can also be blended with each other, to combine properties of their constituent materials including PCL/PGLA 13 and PCL/ chitosan. 14,15 They can be combined with other treatment strategies, such as cell transplants including glia that is, Schwann cells or olfactory ensheathing cells (OECs), neural progenitor cells, or stem cells [16][17][18][19] ; or impregnated with compounds noted for their neurotrophic properties or ability to disrupt the inhibitory scar environment. This combinatorial approach has demonstrated some success in the encouragement of neurite outgrowth or functional recovery, such as the combination of a PCL scaffold with neural progenitor cell implantation and perfusion with chondroitinase ABC, 18 or PCL nanofibers impregnated with the brainderived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers can also be blended with each other, to combine properties of their constituent materials including PCL/PGLA 13 and PCL/ chitosan. 14,15 They can be combined with other treatment strategies, such as cell transplants including glia that is, Schwann cells or olfactory ensheathing cells (OECs), neural progenitor cells, or stem cells [16][17][18][19] ; or impregnated with compounds noted for their neurotrophic properties or ability to disrupt the inhibitory scar environment. This combinatorial approach has demonstrated some success in the encouragement of neurite outgrowth or functional recovery, such as the combination of a PCL scaffold with neural progenitor cell implantation and perfusion with chondroitinase ABC, 18 or PCL nanofibers impregnated with the brainderived neurotrophic factor.…”
Section: Introductionmentioning
confidence: 99%
“…According to our study [13], the PCL-20%CS scaffolds achieved the most superior results for supporting osteoblast proliferation, followed by PCL-10%CS scaffolds and pure PCL scaffolds, respectively. In addition, the following experiments indicated that the cells cultured on the PCL-20%CS scaffolds could produce more mineralized matrixes than those with other proportions.…”
Section: N Thuaksuban Et Al / Repairing Calvarial Defectsmentioning
confidence: 70%
“…In addition, the mechanical testing indicated that the scaffolds are suitable for withstanding forces occurring in real circumstances of the reconstruction in oral and maxillofacial region [14]. Regarding the economical consideration, the cost of the scaffolds is significantly cheaper than importing scaffolds, therefore, MSMD is the main technique for fabricating biodegradable scaffolds in our future studies.According to our study [13], the PCL-20%CS scaffolds achieved the most superior results for supporting osteoblast proliferation, followed by PCL-10%CS scaffolds and pure PCL scaffolds, respectively. In addition, the following experiments indicated that the cells cultured on the PCL-20%CS scaffolds could produce more mineralized matrixes than those with other proportions.…”
mentioning
confidence: 70%
See 2 more Smart Citations